A systematic review to aligning research paths: Energy cyber-physical systems. Issue 1 (1st January 2019) - Orumwense, Efe Francis; Abo-Al-Ez, Khaled
Abstract: Cyber-Physical Systems (CPS) is a new generation of digital technology that is concerned with the integration and inter-dependencies of the cyber and physical world alongside computational elements. As a new and leading technology, its applications are seen in different projects involving energy and this has however generated lots of interest from the industry, researchers in academia and the government. This paper presents an extensive overview and modernistic research on the applications relating to energy CPS and the security issues and challenges revolving around this research path. In order to achieve this, a systematic literature review was carried out which enabled the analysing and classifying of different applications and security issues described in selected publications. Furthermore, the systematic review permitted the discourse stringing these research areas as well as providing future lines of research. Also, results from the review show the paths where there are increasing research focus and expected research trend in the future years to come. These results will not only be useful in serving as a guide to researchers but will also create new research paths to more experienced researchers to actively follow.